2018
DOI: 10.3389/fendo.2018.00405
|View full text |Cite
|
Sign up to set email alerts
|

ANRIL: A lncRNA at the CDKN2A/B Locus With Roles in Cancer and Metabolic Disease

Abstract: The CDKN2A/B genomic locus is associated with risk of human cancers and metabolic disease. Although the locus contains several important protein-coding genes, studies suggest disease roles for a lesser-known antisense lncRNA encoded at this locus, called ANRIL. ANRIL is a complex gene containing at least 21 exons in simians, with many reported linear and circular isoforms. Like other genes, abundance of ANRIL is regulated by epigenetics, classic transcription regulation, splicing, and post-transcriptional infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
167
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 106 publications
(260 reference statements)
4
167
1
2
Order By: Relevance
“…ANRIL is an antisense lncRNA encoded at the CDKN2A/B locus with roles in cancer risks and metabolic diseases, such as type 2 diabetes, coronary artery disease, myocardial infarction, and stroke. 34 Li et al 35 reviewed that the lncRNA ANRIL is an oncogene of various tumors such as gastric cancer, lung cancer, hepatocellular cancer, and esophageal squamous cell cancer. Another study found that ANRIL was upregulated in glioma, promoting cell proliferation, migration and invasion, and inhibiting apoptosis by downregulating mir-34a.…”
Section: Discussionmentioning
confidence: 99%
“…ANRIL is an antisense lncRNA encoded at the CDKN2A/B locus with roles in cancer risks and metabolic diseases, such as type 2 diabetes, coronary artery disease, myocardial infarction, and stroke. 34 Li et al 35 reviewed that the lncRNA ANRIL is an oncogene of various tumors such as gastric cancer, lung cancer, hepatocellular cancer, and esophageal squamous cell cancer. Another study found that ANRIL was upregulated in glioma, promoting cell proliferation, migration and invasion, and inhibiting apoptosis by downregulating mir-34a.…”
Section: Discussionmentioning
confidence: 99%
“…Motterle et al indicated that chr9p21 variation affected the level of CDKN2A through regulating lncRNA ANRIL expression, which modulates the proliferation of vascular smooth muscle cells and enhances AS. 18,20 Therefore, CDKN2A is clearly related to the development of AS. However, whether CDKN2A mediates ox-LDL-induced cell progression in AS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this locus is associated with an increased risk of cancer and metabolic disease, including type 2 diabetes, obesity and cardiovascular diseases 37 . ANRIL expression and function have been extensively investigated in several cancers but not in iCCA 38 .…”
mentioning
confidence: 99%